River phosphorus pollution sensory detection & quantification system - Syed Jefri, Sharifah Nailawafa; Habaebi, Mohamed Hadi; Yusoff, Siti Hajar; Islam, Md. Rafiqul (IEEE, 2021)
Excessive amount of nutrients content such as phosphorus could pollute the river (e.g., organic pollution) and harm the ecosystem, in long term, to eutrophication. Hence, it is essential to monitor and control the concentration of NPK (Nitrogen, Phosphorous, K for Potassium or Potash) elements for sustaining good water quality and reducing water pollution of natural water. Hence, the main idea of this research is to develop an integrated optical sensor to quantify the concentration of phosphorus to reduce river pollution. Design of the optical sensor comprises of LED at specific wavelength for the transmission system and LDR as detection system together with the associated circuitry and power systems and signal analysis is done at the microcontroller. System performance has been very good and is validated against standard lab measurements.